(untitled) (Bombay Hospital Journal, 2024)
Aim-To report a case of thermal burn at an unusual site in the oral cavity. Background-Thermal burns of the oral cavity are caused by accidental ingestion of hot foods and beverages. Most of the cases are minor and treated conservatively but in some cases surgical management is required. Case Description -A 38 year old male had burning sensation of mouth following accidental ingestion of hot liquids and on clinical examination whitish lesions with erythema noted on floor of the mouth.Case was managed conservatively. Conclusion-Prompt management of such a case has to be done.